Effectiveness of oral corticosteroids (prednisolone) in sensorineural hearing loss post COVID-19 - Wessam Mostafa Essawy (The Egyptian Journal of Otolaryngology, 2022)
Abstract Background Numerous infections can result in neurological symptoms, including anosmia, facial paralysis, and abrupt sensorineural hearing loss (SSNHL). During the earlier SARS pandemic, coronaviruses were linked to a loss of smell and taste due to brain damage. Purpose To clinically detect corticosteroid treatment effectiveness in SSNHL post-COVID-19 infection and to detect the factors that affect the prognosis for these patients for better diagnosis and earlier management. Subjects and method Subjects included 20 subjects diagnosed by PCR as COVID-19 virus positive, complaining of sudden onset hearing loss post viral infection in different durations. All subjects had basic audiological evaluation done pre-treatment and repeated after 1 week, 2 weeks, and 1 month after treatment with methylprednisolone 21-acetate tablets. Results Onset of hearing loss post-COVID infection ranged from 1 to 3 months. As regards the improvement recognized with treatment course, thirteen patients (65%) of all twenty patients showed complete improvement at 1 month after starting treatment, and seven patients (35%) showed no improvement even after 1 month. Conclusion SSNHL has been widely recognized in the context of COVID-19 to date. Early corticosteroid therapy could help in the recovery of hearing, especially if the beginning of therapy was early in the first 2 weeks.